Rural versus urban perspectives on behavioral health issues and priorities. Issue 4 (8th August 2017) - Cuthbertson, Courtney A.; Albrecht, Don E.; Loveridge, Scott
Abstract: Local incidence of behavioral health issues such as substance abuse or poor mental health are a topic of increasing concern, but the specific needs, issues, and priorities of cities can differ from those in rural areas. We illustrate how rural and urban perceptions and knowledge may differ with a survey about community behavioral health priorities in Clark County, Nevada. The survey had a 44% response rate and the sample was 77.3% urban. Rural leaders had different behavioral health concerns and received information from different sources than their urban counterparts. Alcohol abuse and illegal drug use were top behavioral health priorities for both groups. Rural leaders cited mental and physical abuse as priorities, while urban leaders prioritized depression and suicide. The findings demonstrate the importance of recognizing that geographic proximity does not equate to identical behavioral health concerns or priorities, which also impacts community use of data for decision-making.